Global Nepticulidae, Opostegidae, and Tischeriidae (Lepidoptera): temporal dynamics of species descriptions and their authors - Dobrynina, Viktorija; Stonis, Jonas R.; Diškus, Arūnas; Solis, M. Alma; Baryshnikova, Svetlana V.; Shin, Young-Min (Zootaxa, 2022)
This study identifies the number of named and described species of three monotrysian, plant-mining lepidopteran families worldwide: Nepticulidae and Opostegidae (Nepticuloidea), and Tischeriidae (Tischerioidea). At the end of 2021, we estimated that a total of 1000 Nepticulidae species, 197 Opostegidae species, and 170 Tischeriidae species have been described since the taxonomic practice of describing species began in the 18th century. We examine and discuss the history of descriptions and authorship of species worldwide for each of the three families. We found that the total (accumulative) number of species described increased with each time period delineated. About five new species were described per year on average, or about 22 new species were described per year in the 21st century. We recognize researchers with the most number of described species in these three taxa.